A Complete Denture By Rapid Prototyping With Reverse Engineering Approach - Ahmad, Mohd Nazri; Wahid, Mohammad Khalid; Maidin, Nurul Ain; Ab Rahman, Mohd Hidayat; Osman, Mohd Hairizal; Alis@Elias, Izzati Fatin (International Journals of Engineering and Sciences Publisher, 2019)
This paper presents a denture fabrication process by implementing the techniques used in the addictive manufacturing which is 3D printing technology involving reverse engineering method. A three dimensional scanner was used to obtain the surface data of the complete partial denture model that received from the dental clinic. The scanned data was refined using the Geomagic Studio and then converted to STL format for CAD and 3D printing application. The complete dentures design was converted to STL format for production of the product using the Projet HD 1000 machine which is one of the rapid prototyping (RP) technique. Cold cure acrylic resin (VERTEX, Castavaria) was used as the denture material on the gum section. On the teeth section, the composite resin will be applied to add an aesthetic value to the part. Then, the final dentures were polished and tested on an edentulous model to test the bite and adaptability. The finished denture has been test to ensure the adaptability and comfortability. Thus, the user felt comfort while tested the printed denture. The method of fabrication by addictive manufacturing is much faster compared to traditional method. The time taken to complete the denture is 5 hours. Otherwise by conventional method consumed about 15 hours. The result for the denture has been checked to ensure satisfactory and good accuracy. Unlike the traditional method of fabrication, this research has potential to reduce fabrication period of time and make it easier to replace a new set of denture that had been broken.